Le transect : outil de dialogue interdisciplinaire et de médiation - Frédéric Pousin; Audrey Marco; Valérie Bertaudière-Montès; Carole Barthélémy; Nicolas Tixier (VertigO)
The construction of a new infrastructure on a territory is commonly dealt with in a dual logic: The layout on one hand, and the compensation of occasional pollutions on the other. More generally, it raises a set of issues that stimulates several research fields such as ecology, socio-ethnology of usages, and landscape urbanism. There is a challenge for the development of the 21st century territories in connecting these fields, in articulating them in theory and through action. Based on the research D-TRANSECT – programming ITTECOP 2012, this article outlines the methodology of the urban transect, a sensitive methodology that captures in one single gesture the different stakes specific to each of the research fields involved in an infrastructure project. Such a methodology enables us to develop a tool capable of organizing a multi-stakeholder debate around the sites of projects that are not determined right away by the layout of the infrastructure, but rather defined by taking advantage of opportunities in the territory, particularly the wastelands. So the infrastructure project goes beyond just the project of a layout. It opens towards project forms that can’t just be expressed in the space of a plan and requires new tools and procedures of expression. Through three different types of transects, the article will analyze the advantages of the transect as a tool for interdisciplinary dialogue. How do the approaches make the disciplines interact and alter one and another? It will also analyze the advantages of the transect as a tool for dialogue among the many stakeholders (experts, residents, professionals). Finally, it will show how such a dialogue, embedded in an original “long table”, helps to anchor the projects in a participatory process that renews the consultation practices.